The Airbnb way : 5 leadership lessons for igniting growth through loyalty, community, and belonging - Michelli, Joseph A., 1960- (McGraw-Hill, 2020)
"New from bestselling author Joseph Michelli! How Airbnb has disrupted the hospitality industry for unparalleled success-critical lessons that apply to any 21st Century business. No one understands better than Joseph Michelli how businesses create and leverage world-class customer experiences. Over the past decade, Michelli has guided businesses in human experience transformation and revealed how Starbucks, Zappos, Mercedes, and other top companies design and execute the strategies that made them the undisputed leaders of their industries. Now, Michelli turns his attention to major disrupter, Airbnb. In The Airbnb Experience, he shows how innovative leaders have managed to build an unique brand by inspiring and engaging a community of hospitality entrepreneurs-a feat unparalleled in the shared economy. Inside, you'll find: Airbnb's strategies and practices that drive customer engagement and loyalty, how to provide phenomenal customer service in the shared economy, proven principles for getting the most from all stakeholders-including those who share resources and services, exclusive interviews with Airbnb leaders, hosts, and guests that provide invaluable information for your business. The shared economy is the future, but it introduces business challenges never before faced: how do you serve a broad range of customers across varying geographies through a distributed network of 'partners'? Airbnb has solved the puzzle, and Michelli shows you all the pieces-and how they fit together"--